Evaluation of the Knowledge and Awareness of Firefighters in Turkey in Disaster Risk Management - Utuk, Ayse; Baracli, Hayri (MDPI, 2024)
Firefighters stand as one of the most effective task forces, striving to minimize losses incurred during disasters. Clarifying the present status of disaster risk management for firefighters can offer insights into the factors influencing response during disasters and how preparedness for such events can be enhanced. The aim of this study is to assess the current status of fire and rescue services, actively engage in crisis management during disaster risk management, to identify areas for improvement that enhance their involvement in preparatory stages, and to bolster their effectiveness in crisis management. This descriptive, cross-sectional study involved 772 firefighters who had prior experience in disaster response. The findings of this study revealed that firefighters who had undergone first aid training demonstrated the ability to anticipate hazardous situations and behaviors, regularly inspected their equipment, showed awareness of work-related accidents and occupational diseases, and scored statistically higher on the scales. These findings are expected to assist fire departments in establishing a sustainable and comprehensive disaster management cycle.
Keywords: risk management; integrated disaster management; sustainable disaster cycle; OHS; firefighter; effectiveness; HEALTH-PROFESSIONALS; PREPAREDNESS; EMERGENCY; NURSES; RESILIENCE; KATRINA; LEVEL; Science & Technology - Other Topics; Environmental Sciences & Ecology